Specialty Meat Marketing Claims: What's the Difference? - Chad Carr; Larry Eubanks; Ryan Dijkhuis (EDIS)
American consumers are confused about the differences between meat products with special marketing claims (i.e., organic, natural, naturally raised, and grass-fed) and regular or commodity meat products. This revised 5-page report discusses these claims as defined by the USDA and addresses the differences between these products for food safety, human health, and eating quality. Written by Chad Carr, Larry Eubanks, and Ryan Dijkhuis and published by the UF Department of Animal Science, April 2011.